Phytochemical, pharmacological, pharmacokinetic and toxicological characteristics of Ziziphi Spinosae Semen: a review - Liu, Mei-Hua; Jin, Hong-Xin; Song, Zhen; Wang, Jing-Yi; Gao, De-Jiang (Frontiers in Pharmacology, 2024)
Ziziphi Spinosae Semen (ZSS) is the seeds of Ziziphus jujuba Mill. var. Spinosa (Bunge) Hu ex H. F.Chou, which has the effects of nourishing heart and liver, tranquilizing heart and tranquilizing mind.With the development of research on the metabolites of ZSS, more than 160 metabolites have been isolated from ZSS, including saponins, alkaloids, flavonoids, fatty acids, volatile oils, polysaccharides and proteins. The active metabolites of ZSS have regulatory effects on the nervous system, cardiovascular system, hematopoietic system, immune system and substance metabolism, and have various pharmacological effects such as anti-oxidation, anti-aging and anti-cancer.Although many traditional uses of ZSS have been clarified, the relationship between its structure and function remains to be further studied. This article provides a review of the metabolites, pharmacological activity, pharmacokinetics and toxicology of ZSS, and explores the future research prospects and existing problems of ZSS, so as to provide reference for further research and establishment of quality control standards of ZSS. MetabolitesThe chemical composition of ZSS is complex and diverse. To date, more than 160 metabolites have been isolated and identified from ZSS, primarily including saponins, flavonoids, triterpenoids, alkaloids, fatty oils, steroids, phenolic acids, amino acids, and trace elements.